Cadmium and zinc accumulation behaviour of hyperaccumulator Arabidopsis halleri ssp. gemmifera in the hydroponic system - Syarifah Hikmah Julinda Sari; Mei-Fang Chien; Chihiro Inoue (Journal of Degraded and Mining Lands Management, 2023)
Arabidopsis halleri ssp. gemmifera is classified as Cd and Zn hyperaccumulator plant, however, the disparity accumulation preferences in organs (root, stem and leaves) between cadmium and zinc seems less understandable. Therefore, this study aimed to portray accumulation behaviour toward the presence of Cd and Zn in the hydroponic method employing A. halleri ssp. gemmifera. The experiment was conducted by applying this plant using 2 and 300 µM of Cd, and 2 and 200 µM Zn, together with 20% Hoagland solution for 7 days, separately. The results showed that Zn in the medium was uptake faster than Cd. Furthermore, increasing Cd/Zn supply at the medium resulted in an increasing accumulation of Cd/Zn in the organs of the plant. In both Cd treatments, the accumulation followed the order of stem>root>leaves, indicating Cd transportation to the upper part has occurred during this period. The same accumulation preference pattern was also reported in the 200 µM Zn supply. However, at 2 µM Zn supply, Zn accumulation was mainly found in the leaves, followed by the root and stem. A. halleri ssp. gemmifera uptake Zn faster from the medium and translocate rapidly to the leaves at low-level Zn supply. Increasing Zn supply concentration might inhibit the translocation of Zn from stem to leaves. Meanwhile, regardless of Cd supply concentrations, this plant could only translocate Cd to the stem mostly within a short-time exposure period. Therefore, this study concluded that A. halleri ssp. gemmifera exhibited different accumulation responses when exposed to different Cd and Zn supply concentrations.